Armet transcript knockdown in Tribolium castaneum - Bechard, Jarrod (Kansas State University, 2014)
Armet has been found in mammalian systems to be a bi-functional protein that is secreted extracellularly and is also found in the endoplasmic reticulum. It has been shown to be a neurotrophic factor and also a member of the unfolded protein response. Transcript knockdown of Armet via RNA interference in late instar larvae of Tribolium castaneum produces a fatal phenotype during eclosion from pupa to adult. Initial observations of pupae cuticle indicate disorganization of cuticles in insects with the Armet transcript knocked down. Here I expand studies on the effects of dsArmet RNA injection; both in a wild type strain and a fluorescent strain of Tribolium, and discuss possible mechanisms for the fatal phenotype.
Keywords: Tribolium castaneum; RNAi; Armet; Cuticle